The effect of foreign direct investment (FDI) on agriculture and economic growth in Malaysia / Farahdilah Amir - Amir, Farahdilah (2012)
In this paper, the effect of Foreign Direct Investment (FDI) on Agriculture and Economic Growth are examined. The aim of this paper is to examine the effect by FDI on the Agriculture and Economic Growth in Malaysia based on econometric models. The studies on Malaysia by using World Bank Data Catalogue and Department of Statistic Malaysia data from 1980 to 2010 which consist 30 years length. It is observed that FDI has a positive effect on Agriculture and Economic Growth but then. The study recommends rethinking the higher technology on this sector and setup for increasing the productivity and growth of agriculture just like economic growth effected by FDI. An important implication of the results is that only GDP and Agriculture have a short term affected, furthermore FDI more affected on GDP than Agriculture.